Energy efficient refrigeration system with simultaneous heating and cooling. (2021) - Nikhil Babu, P.; Mohankumar, D.; Manoj Kumar, P.; Makeshkumar, M.; Gokulnath, M.; Gurubalaji, K.; Harrish, G.; Ashok, M.
Abstract: Refrigeration is a process of providing and maintaining temperature below the atmosphere. The medium used for refrigeration process is called as refrigerant. In normal refrigeration system, the heat rejected in condenser is getting wasted. We have the potential to utilize the heat rejection from the condenser. This rejected heat can be used for domestic purposes, like heating water, bathing, washing clothes and pots. The main advantage of simultaneous heating and cooling is that it can be carried out from one vapour compression refriegration (VCR) system. The effectiveness of refrigeration system relies on the refrigerant properties. However, the refrigerants used in present the world are having high potential to produce Global Warming and Ozone Depletion. The use of an eco-friendly alternative refrigerants may help to reduce the potential of Global Warming and Ozone Depletion. In this investigation, an analysis of the VCR System is conducted with two alternative refrigerants, R290 and R134a. The experiments were performed to determine the COP of the system and cooling capacity with simultaneous heating and cooling, where we had also been finding out the amount of waste heat generated at the condenser using both the refrigerants. The results showed that (COP)cooling of R134a was lower that R290 at an average of 16.43% and thereby making it more efficient for this system. Also, (COP)heating value of R134a was 18.27% less than that of R290 and cooling effect of R134a was lower than 12% from R290. All the obtained results were compared graphically.